1993
DOI: 10.1044/jshr.3605.927
|View full text |Cite
|
Sign up to set email alerts
|

The Need for Replication

Abstract: Replication provides verification and disconfirmation functions for the scholarly fields. Relatively few replications were found in a survey of studies in JSHD and JSHR over a recent decade. Based on the probabilities of Type I and Type II errors, there are likely to be approximately 50 to 250 false findings in this literature. Because many studies had relatively small sample sizes, replication would be helpful for extending the generalization of their results. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 11 publications
4
32
0
Order By: Relevance
“…Millard et al [4] (2008) reported that 4 out of 6 children in their study (60%) were “cured” and discharged through indirect PCIT. The consistency of the results of this study with the previous studies supports more powerfully the use of indirect treatment programs for these groups of children [52, 53]. …”
Section: Discussionsupporting
confidence: 80%
“…Millard et al [4] (2008) reported that 4 out of 6 children in their study (60%) were “cured” and discharged through indirect PCIT. The consistency of the results of this study with the previous studies supports more powerfully the use of indirect treatment programs for these groups of children [52, 53]. …”
Section: Discussionsupporting
confidence: 80%
“…Therefore, corroboration with a larger sample size via direct replication is warranted [14]. Replication provides two basic functions essential for the substantive base of any scholarly field: verification and disconfirmation, i.e., a fact is not a fact until it is replicable [14]. Specific to the current issue, a causal relationship exists when a tracheotomy is a sufficient condition for the occurrence of aspiration.…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of this systematic replication study [19], i.e., replication of a study with minimal variations in design, was to determine if a clinical swallowing examination consisting of six identi®ers of aspiration risk, i.e., dysphonia, dysarthria, abnormal gag re¯ex, abnormal volitional cough, cough after swallow, and voice change after swallow [12], would have acceptably high risk assessment values to predict aspiration risk in the acute stroke population when compared with an instrumental ®beroptic endoscopic evaluation of swallowing (FEES) [20,21].…”
mentioning
confidence: 99%